STUDY ON THE EFFECTS OF MELATONIN ADMINISTRATION ON INFLAMMATORY AND OXIDATIVE STRESS MARKERS IN PATIENTS WITH TYPE II DIABETES AND PERIODONTAL DISEASE - Diana-Maria Anton; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Raluca Mocanu; Ionut Luchian; Monica-Mihaela Scutariu; Liliana Pasarin; Silvia Martu (Romanian Society of Oral Rehabilitation, 2022)
The aim of this study was to evaluate the effects of melatonin supplementation accompanied by non-surgical periodontal therapy on serum melatonin, as well as inflammatory and oxidative stress markers in patients with type 2 diabetes with chronic periodontitis. The study was conducted on 50 subjects with periodontitis and diabetes mellitus type 2 (study group n = 25: patients with scaling and root planing + melatonin; control group = 25: patients with scaling and root planing + placebo). The melatonin, interleukin 6 (IL-6), tumour necrosis factor alpha (TNF-α) and high-sensitivity C-reactive protein (hs-CRP), total antioxidant capacity (TAC) and total serum oxidant (TOS) levels were measured at baseline and after 8 weeks. Melatonin systemic intake reduced inflammation and oxidative stress markers in diabetic patients with chronic periodontitis.